The reality of bullying act within schools in Mafrak City’s public District from the point of view of principals - Alrmilat, Victoria Oudeh (Journal of Educational and Psychological Sciences, 2021)
The objective of the study was The reality of bullying act within schools in Mafrak City’s public District from the point of view of principals order to achieve the aim of the study, The current study aimed to identify the reality of bullying in public schools of the Kasbah of Mafraq from the point of view of school principals in them, and to achieve the aim of the study, a descriptive approach was used, where a questionnaire was developed consisting of four areas with (19) paragraphs, and its validity and consistency was confirmed, and then it was distributed. On the intended study sample consisting of (147) principals and principals in the Kasbah of Mafraq schools. The results of the study showed that the degree of estimation of the reality of bullying in public schools of the Kasbah of Mafraq from the point of view of the study sample was of a medium degree, with an arithmetic average (2.17). The results also showed that there are no statistically significant differences in the estimates of the study sample individuals due to the gender variable at the total level of the tool and in all dimensions. In light of the results, the researcher recommended the necessity of increasing communication between the school and the home through the establishment of many workshops to prevent the dangers of bullying and the involvement of students and teachers in cultural and social activities and programs aimed at giving them opportunities for positive social communication, and the school administration’s establishment of awareness and educational courses for teachers and parents to increase their awareness Activating the role of educational counseling in schools, following up on students on a regular basis, and conducting more educational research and studies that examine the reality of bullying in the public and private schools of the Kasbah of Mafraq.